The Effect of Special Exercises Proposed In the Development of Right-Wing Punch Force in the Team of the Faculty of Physical Education and Sports Sciences of Boxing - Abbas, ElafRabeea (International Journal of Psychosocial Rehabilitation, 2020)
The introduction to the research and its importance in training boxers came to develop striking strength in basic boxing skills through the development of exercises. The research problem came from a weakness in the punch strength in the majority of boxers, which led to a fluctuation in performance, and this appeared in the recent disturbances between our college and Diwali University, so the researcher suggested developing exercises. A proposal to develop the right-punching force. The aim of the research is to determine the number of suggested exercises and determine their effect on the development of straight-blow strength. In the College of Physical Education and Sports Sciences, there are statistically significant differences between the pre- and remote tests in the experimental research sample in developing the right punching force. The researcher used the experimental approach to deal with the research problem, as well as adopting the same one-group method: experimental with two tests: before and far. The College of Education and Sports Sciences, University of Baghdad; its number is (12). The researcher concluded that the training curriculum developed by the researcher had a positive effect on the multiplication strength in the sample. The researcher recommended applying the training curriculum to all Iraqi boxing teams in order to play an active and positive role in increasing the efficiency of hitting force.